Can fear of failure predict academic procrastination? A study of Indonesian university students - Nur Fauziah Karim; Minarni; Syahrul Alim (Institut Agama Islam Negeri Langsa, 2021)
This study aims to determine the ability of fear of failure in predicting academic procrastination in students in Indonesia by involving 428 respondents (male = 52.63%). The instruments used are the academic procrastination scale and the fear of failure scale. Analysis of this research data uses a simple linear regression technique. This study showed that fear of failure affected academic procrastination significantly with a contribution value of 38.6% positive direction, while 61.4% was influenced by other factors not studied. Research confirms that students with high levels of fear of failure tend to have high levels of academic procrastination and vice versa